STUDENTS’ PERCEPTIONS ON MOBILE LEGENDS: BANG-BANG (MLBB) AS MEDIUM TO LEARN ENGLISH - Dewi Christa Kobis; Michel Farrel Tomatala; Dewi Christa Kobis (LINGUA : JURNAL ILMIAH, 2020)
This study aims to know students’ perceptions on the role of Mobile Legends: Bang-Bang (MLBB) as the medium to learn English. This study explores MLBB as a possible training center where all skills which are necessary to learn English such as vocabulary, listening, reading, writing and speaking had been learned through the process of playing the game. This study uses quantitative and qualitative methods where questionnaire and interviews are employed to find the answers for all research questions. The respondents of this study were 31 freshmen students in STMIK Multicom Bolaang Mongondow who took Information Technology as their major. This study found that the majority of respondents perceive MLBB as an effective medium to learn English. 58.1% claimed that MLBB enriched their vocabulary, 61.3% claimed that MLBB helps them in listening practice, 58.1% claimed that they can read and spell English well after playing MLBB, 48.4% claimed that MLBB helps them in writing, and 67.7% claimed that MLBB helps improving their English pronunciation and speaking skill.